2009
DOI: 10.1038/nchembio.275
|View full text |Cite
|
Sign up to set email alerts
|

Reduced histone deacetylase 7 activity restores function to misfolded CFTR in cystic fibrosis

Abstract: Chemical modulation of histone deacetylase (HDAC) activity by HDAC inhibitors (HDACi) is an increasingly important approach to modify the etiology of human disease. Loss-of-function diseases arise as a consequence of protein misfolding and degradation leading to system failures. The ΔF508 mutation in cystic fibrosis transmembrane conductance regulator (CFTR) results in the absence of the cell surface chloride channel and a loss of airway hydration, leading to premature lung failure and reduced lifespan respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
250
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(264 citation statements)
references
References 48 publications
13
250
1
Order By: Relevance
“…These included drugs approved for non-CF indications [e.g., 4-phenylbutyrate, miglustat, sildenafil, suberoylanilide hydroxamic acid (SAHA)] (19,(30)(31)(32) and compounds identified through high-throughput screening (e.g., corr-4a, VRT-325) (18,19). The cultured F508del-HBE cells were preincubated with each compound at the maximally effective concentration and treatment duration (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These included drugs approved for non-CF indications [e.g., 4-phenylbutyrate, miglustat, sildenafil, suberoylanilide hydroxamic acid (SAHA)] (19,(30)(31)(32) and compounds identified through high-throughput screening (e.g., corr-4a, VRT-325) (18,19). The cultured F508del-HBE cells were preincubated with each compound at the maximally effective concentration and treatment duration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several CFTR correctors have been previously reported to be active in vitro, including drugs approved for non-CF indications (e.g., 4-phenylbutyrate, miglustat, sildenafil, SAHA) (19,(30)(31)(32) and compounds identified through high-throughput screening (e.g., corr-4a, VRT-325) (18,19). Therapies for CF have not advanced from these efforts, possibly due to insufficient restoration of CFTR function and/or poor selectivity for processing of CFTR compared with other proteins and other off-target actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifi cally, we have shown that the pan Class I/II/IV HDACi suberoylanilide hydroxamic acid (SAHA) restores the secretion and activity of Z-AAT to ~50 % of the level that observed in WT AAT [ 27 ]. Currently, this correction appears to be mainly through inhibition of HDAC7, which is the same HDAC target that can be modifi ed by SAHA to correct the folding of the most common mutation found in cystic fi brosis, F508del [ 249 ]. Incubation with SAHA or silencing of HDAC7 improves AATD through multiple pathways.…”
Section: Therapeutic Intervention Through the Acetylationdeacetylatiomentioning
confidence: 99%
“…Given the above, it is therefore not surprising that HDAC inhibitors (HDACi) have been shown to have benefi cial effects for ma ny protein misfolding diseases, such as cystic fi brosis [ 249 ], Gauchers disease [ 250 ], muscle atrophy [ 251 ], Niemann-Pick C [ 252 , 253 ], and neurodegenerative diseases [ 254 -258 ]. Specifi cally, we have shown that the pan Class I/II/IV HDACi suberoylanilide hydroxamic acid (SAHA) restores the secretion and activity of Z-AAT to ~50 % of the level that observed in WT AAT [ 27 ].…”
Section: Therapeutic Intervention Through the Acetylationdeacetylatiomentioning
confidence: 99%